2018
DOI: 10.1002/pssr.201800319
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient, Scalable Route to Robust PVDF‐co‐HFP/SiO2 Separator for Long‐Cycle Lithium Ion Batteries

Abstract: A highly uniform, heterogeneous-phase composite separator is synthesized by a direct post-solidation process from the mixture of nano-SiO 2 /acetone monodisperse suspension and poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-co-HFP)/acetone gel, without any organic surfactants. This technique leads to the PVDF-co-HFP/SiO 2 composite separator outstanding microstructural uniformity. The incorporation of SiO 2 nanoparticles leads to reduced crystallinity (%27%), enhanced wettability (%14%), improved elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…The modification of particles before their use in polymer matrices gave intended results, but this approach is time‐consuming, expensive, and complicated for commercial viability. Boateng et al reported highly uniform PVDF‐HFP/SiO 2 composite separator prepared from the mixture of PVDF‐HFP/acetone gel and nano‐SiO 2 /acetone monodispersed suspension without any use of a surfactant with facile, cost‐effective, and scalable route. The reported separator exhibits high thermal stability (4.5% thermal shrinkage upon heating at 160 °C for 1 h), robust mechanical strength (14 MPa), enhanced ionic conductivity, and remarkable electrochemical capabilities with long cycle performances.…”
Section: Types Of Separatorsmentioning
confidence: 99%
“…The modification of particles before their use in polymer matrices gave intended results, but this approach is time‐consuming, expensive, and complicated for commercial viability. Boateng et al reported highly uniform PVDF‐HFP/SiO 2 composite separator prepared from the mixture of PVDF‐HFP/acetone gel and nano‐SiO 2 /acetone monodispersed suspension without any use of a surfactant with facile, cost‐effective, and scalable route. The reported separator exhibits high thermal stability (4.5% thermal shrinkage upon heating at 160 °C for 1 h), robust mechanical strength (14 MPa), enhanced ionic conductivity, and remarkable electrochemical capabilities with long cycle performances.…”
Section: Types Of Separatorsmentioning
confidence: 99%
“…Lithium ion batteries (LIBs) are generally prioritized due to multiple promising features like better density (energy), improved flexibility, less weight, effective self‐discharge rate, high current density, environmental benignity, and more battery life 6‐10 . The mentioned attractive properties of LIBs pave its path to be a strong candidate for applications like smart phones, laptops, renewable power stations, defense arsenal, subsurface investigation, space vehicles, and heat‐reactors.…”
Section: Introductionmentioning
confidence: 99%
“…benignity, and more battery life. [6][7][8][9][10] The mentioned attractive properties of LIBs pave its path to be a strong candidate for applications like smart phones, laptops, renewable power stations, defense arsenal, subsurface investigation, space vehicles, and heat-reactors. LIBs have been developed with good pace, both in research and commercialization from the last three decades.…”
mentioning
confidence: 99%
“…The separator outperformed commercial separators, showing high rate capacitieso f 104.8 mAh g À1 at 5C and 95 mAh g À1 at 10 Ca sw ell as unparalleled perfect capacity retention at 10 Cafter 1000cycles. [21][22][23] The electrolyte uptake ratios of the separators (M-0, M-0.5, M-1, M-1.5,and Celgard 2320) are 180.58, 114.81, 108.63, 106.43, and 86.67 %, respectively.T he PVDF-HFP separators absorb more electrolytes than Celgard2320. [3,18,19] As shown in Figure 1i,j,t he contacta ngle of Celgard 2320 is 458 whereas M-0.5 shows al ower contact angle of 188 in the early stage of electrolyte contacting (t = 2s), which verifies that M-0.5 shows better wettability owing to its strong cross-linked, inner-bound, and tortuous porous structure.…”
Section: Introductionmentioning
confidence: 99%
“…[20] High electrolyte uptake,c aused by high porosity and electrolyte wettability of the separator,improves the rate capability and long-term stabilityb yf acilitating ionic shuttling across the separator and reducing electrode/electrolyte interfacial resistance. [21][22][23] The electrolyte uptake ratios of the separators (M-0, M-0.5, M-1, M-1.5,and Celgard 2320) are 180.58, 114.81, 108.63, 106.43, and 86.67 %, respectively.T he PVDF-HFP separators absorb more electrolytes than Celgard2320. Nonetheless, the electrolyte uptake of the prepared separators decreases with increasing amount of NMP because of the reduced porosity.…”
Section: Introductionmentioning
confidence: 99%